Cuneiform in Canaan the next generation - Horowitz, Wayne 1957-; Oshima, Takayoshi 1967-; Sanders, Seth L. 1968- (Eisenbrauns, 2018)
"Presents the full corpus of all 91 cuneiform tablets and inscribed objects that have been recovered from the Land of Israel, including cuneiform tablets from the Bronze Age cities of Canaan, texts from the cities of the Philistines, and inscriptions from the Kingdoms of Judah and Israel"...Provided by publisher